Asymmetric Sulfa-Michael Addition of α,β-Unsaturated Esters/Amides Using a Chiral N-Heterocyclic Carbene as a Noncovalent Organocatalyst - Yuan, Pengfei; Meng, Sixuan; Chen, Jiean; Huang, Yong (Synlett, 2016)
We report an asymmetric sulfa-Michael reaction of α,β-unsaturated amides and esters using a chiral N-heterocyclic carbene as the HOMO-raising organocatalyst. We discovered an interesting correlation between 13C NMR shifts of substrates and ee of their products. More electron-deficient Michael acceptors afforded higher enantioselectivity.
Keywords: N-heterocyclic carbenes; noncovalent catalysis; sulfa-Michael; organocatalysis; asymmetric synthesis